Bilateral Kuttner tumor of submandibular glands; a case report and review of the literature - Noppadol Larbcharoensub (2018)
Kuttner tumor is a relatively uncommon disease of the salivary gland. It is also known as chronic sclerosing sialadenitis or cirrhosis of the submandibular gland. The examination of the submandibular gland characterizes clinically by a firm swelling of the gland, and histologically by progressive periductal sclerosis, dense lymphocytic infiltration with lymphoid follicle formation, reduction of the secretory gland parenchyma and fibrosis. Clinical, cytologic, histopathologic and immunohistopathologic features with briefly reviewed relevant literature describing 231 cases are discussed. The patients with the mean age of 44 years (range 13-81 years) had submandibular masses known to be present for 1 week to 55 years (mean 23.2 years). There is a slight predilection for occurrence in men. This is the first reported description of bilateral Kuttner tumor of submandibular glands in Thailand. It was initially diagnosed as a primary submandibular gland neoplasm that fine needle aspiration revealed to be chronic sialadenitis.